Efficient and Stable Photoassisted Lithium-Ion Battery Enabled by Photocathode with Synergistically Boosted Carriers Dynamics - Zelin Ma; Shiyao Wang; Zhuangzhuang Ma; Juan Li; Luomeng Zhao; Zhihuan Li; Shiyuan Wang; Yazhou Shuang; Jiulong Wang; Fang Wang; Weiwei Xia; Jie Jian; et al. (Nano-Micro Letters, 2024)
Highlights Developing a universal bulk heterojunction strategy to create oxygen vacancies by embedding laser-manufactured metal nanocrystals into the TiO2 matrix. Proposing a new mechanism based on plasmonic-induced hot electron injection and enhanced conductivity from Schottky contact-derived oxygen vacancies. Establishing several benchmark values for the performance of TiO2-based photocathodes in photoassisted lithium-ion batteries.